QR SCANNING FOR FINAL EXAM ATTENDANCE - Muhammad Haniff, Muhammad Qaisan (IRC, 2019)
During every end of semester, Universiti Teknologi PETRONAS (UTP) has set that every student must attend the final examination before completing the course for the semester. On average, there are around 1500 that will be taking examinations every day during the examination period. The proposal is written for the development of QR Code Final Examination Attendance System for UTP. The attendance system in UTP for final examination is still paper-based even though attendance system for classes have already been integrated to QR Code based system. The aim of this system is to enhance the current paper-based system and improve the facilities within UTP by using QR Code to record the student’s attendance. To complete this project, two phases of methodology are being use which are preliminary studies and system development. To conduct the preliminary studies, literature review of the project and interviews the stakeholders will be done. For system development, Agile methodology will be implemented for the System Development Life Cycle (SDLC) technique and the project will be going through four phases which are Planning, Analysis, Design and, Development and Testing.